Active control of viscous fingering using electric fields - Tao Gao; Mohammad Mirzadeh; Peng Bai; Kameron M. Conforti; Martin Z. Bazant (Nature Communications, 2019)
When a viscous fluid is displaced by a less viscous phase between two plates, a finger-like instability occurs. Here the authors demonstrate how applying an external electric field can suppress the fingering instability without the need to alter the fluid flow rate or the gap geometry.